Low meprin α expression differentiates primary ovarian mucinous carcinoma from gastrointestinal cancers that commonly metastasise to the ovaries. Issue 6 (5th July 2006) - Heinzelmann-Schwarz, Viola A; Scolyer, Richard A; Scurry, James P; Smith, Alison N; Gardiner-Garden, Margaret; Biankin, Andrew V; Baron-Hay, Sally; Scott, Carolyn; Ward, Robyn L; Fink, Daniel; Hacker, Neville F; Sutherland, Robert L; et al.
Abstract : Background: Currently, no specific immunohistochemical markers are available to differentiate primary mucinous epithelial ovarian cancer (MOC) from adenocarcinomas originating at other sites that have metastasised to the ovary, which may have an impact on patient management and prognosis. Aim: To investigate the expression of two intestinal markers, galectin 4 and meprin α, in mucinous carcinomas of the ovary and gastrointestinal tract. Methods: Using immunohistochemical analysis, the expression of galectin 4 and meprin α was investigated in 10 MOCs and in 38 mucinous adenocarcinomas of colon, pancreas, stomach and appendix, the most common sites of origin of ovarian metastases. Results: Total cytoplasmic galectin 4 expression was relatively consistent between the different carcinomas. Membranous meprin α expression was significantly lower in MOCs compared with gastrointestinal carcinomas. Moreover, meprin α expression showed greater discrimination between the ovarian and gastrointestinal carcinomas than the cytokeratins CK7 and CK20, the current standard immunohistochemical markers used to determine the tissue origin of mucinous carcinomas involving the ovaries. Conclusions: Meprin α is a useful additional marker in differentiating primary from secondary mucinous adenocarcinomas of the ovary.